Wariacja Na Wiolonczele Solo - Rek, Aleksandra (Poland : Wajda Studio, 2016)
Dominik Połoński is an eminent musician who survived cancer, his struggle with the disease left its mark, partial paralysis, and the artist can now use only one arm. This, however, did not prevent him from returning to practicing and performing concerts, although his repertoire has changed. Połoński is no longer able to perform virtuoso compositions. But he finds fulfilment as a performer playing contemporary pieces in which he experiments with the instruments abilities. A story of a powerful will that allowed Dominik to overcome the severe limitations he was faced with.
Verzio Film Festival Submission
Keywords: Documentary films